2020
DOI: 10.1371/journal.pone.0229431
|View full text |Cite|
|
Sign up to set email alerts
|

Real-time feedback improves chest compression quality in out-of-hospital cardiac arrest: A prospective cohort study

Abstract: Background Current guidelines underline the importance of high-quality chest compression during cardiopulmonary resuscitation (CPR), to improve outcomes. Contrary to this many studies show that chest compression is often carried out poorly in clinical practice, and long interruptions in compression are observed. This prospective cohort study aimed to analyse whether chest compression quality changes when a real-time feedback system is used to provide simultaneous audiovisual feedback on chest compression quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
3
24
0
1
Order By: Relevance
“…QCPR Classroom was found to help students obtain high-quality CPR training, especially in terms of correct compression depth and full recoil [ 44 ]. Other research studying the influence of received feedback on CPR quality [ 45 , 46 ] reported similar conclusions.…”
Section: Discussionsupporting
confidence: 62%
“…QCPR Classroom was found to help students obtain high-quality CPR training, especially in terms of correct compression depth and full recoil [ 44 ]. Other research studying the influence of received feedback on CPR quality [ 45 , 46 ] reported similar conclusions.…”
Section: Discussionsupporting
confidence: 62%
“…QCPR Classroom was found to help students obtain high-quality CPR training, especially on correct compression depth and full recoil [35]. Other research studying the in uence of received feedback on CPR quality [36][37] have reported similar conclusions.…”
Section: Discussionmentioning
confidence: 62%
“…The feedback sensor is placed on the patient's sternum during resuscitation. The feedback system issues auditory and visual prompts if deviations from the guideline recommendations are detected [21]. The quality of mechanical chest compression is recorded by the corpuls cpr.…”
Section: Exclusion Criteriamentioning
confidence: 99%